2020
DOI: 10.3390/min10121113
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Data and Fluid Inclusion Study of the Middle Miocene Halite from Deep Borehole Huwniki-1, Situated in the Inner Zone of the Carpathian Foredeep in Poland

Abstract: The geochemical data and the study of fluid inclusions in primary halite are invaluable sources of saline basin information. Most of the previous analyses of salt from the Carpathian area have been obtained by studying the halite samples collected from depths not exceeding 1000 m (i.e., from salt mine outcrops or boreholes). In this article, for the first time, we present the results of samples obtained from a deep well where salt occurs below the frontal orogenic wedge at a depth of ~5000 m. The salt core’s p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Features such as halite recrystallization, low bromine content, and the high-temperature homogenization of fluid inclusions indicate that post-depositional transformations played an important role in the formation of the Lotsberg salt deposits. Subsequently, the paper by Bukowski et al [4] presents petrological and geochemical studies of the rock salts and content of major ions in fluid inclusions of primary sedimentary halites from the Carpathian area. The results confirmed that it is possible to preserve primary halite sedimentary structures at great depths (~5000 m), and their inclusion chemistry has not changed.…”
mentioning
confidence: 99%
“…Features such as halite recrystallization, low bromine content, and the high-temperature homogenization of fluid inclusions indicate that post-depositional transformations played an important role in the formation of the Lotsberg salt deposits. Subsequently, the paper by Bukowski et al [4] presents petrological and geochemical studies of the rock salts and content of major ions in fluid inclusions of primary sedimentary halites from the Carpathian area. The results confirmed that it is possible to preserve primary halite sedimentary structures at great depths (~5000 m), and their inclusion chemistry has not changed.…”
mentioning
confidence: 99%